Avoidable Cost Concept on Reducing Production Costs of Refillable Drinking Water Industry SME - Rustan, Rustan; Rum, Muh.; Hamkah, Hamkah (Atestasi : Jurnal Ilmiah Akuntansi, 2024)
Production costs are related to the determination of selling prices so they need to be controlled to control prices in the market. Production costs affect the level of profitability of the company. The purpose of this study is to exploit the extent to which avoidable costs can be reduced in determining production costs. By making some adjustments to production costs such as making efficiency, the production amount of the company's profitability can increase compared to the production costs that are still high. The research was conducted in several small industry-based refillable drinking water industries in the Moncong Loe Region. The analysis technique used is descriptive quantitative with cost accounting calculation method. The results showed that there is a possibility of avoiding some production costs of the refill drinking water industry. Because ineffective costs can be reduced. Based on the evaluation, it can be seen that the production costs applied so far are still high by the indirect raw material costs used. Indirect labor costs also exist but are still seen as costs for routine work. Thus, production costs can be controlled by avoiding some costs so that the selling price can be reduced.